2023
DOI: 10.3390/cells12040620
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Actions in Placental Vascular Morphogenesis and Spiral Artery Remodeling: A Comparative View between Humans and Mice

Abstract: Estrogens, mainly 17β-estradiol (E2), play a critical role in reproductive organogenesis, ovulation, and fertility via estrogen receptors. E2 is also a well-known regulator of utero-placental vascular development and blood-flow dynamics throughout gestation. Mouse and human placentas possess strikingly different morphological configurations that confer important reproductive advantages. However, the functional interplay between fetal and maternal vasculature remains similar in both species. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 164 publications
0
9
0
2
Order By: Relevance
“…The study demonstrated significant differences in statistical parameters between the PreM and PostM groups ( Table S5 ). The absence of estrogen in the PostM group restricts the division and maturation of vascular endothelial cells, 25 leading to a decrease in the submucosal vessels in the urethra. Additionally, there were more vaginal deliveries in the PostM group than in the PreM group, which can cause damage to the urethral tissue and the blood vessels embedded in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated significant differences in statistical parameters between the PreM and PostM groups ( Table S5 ). The absence of estrogen in the PostM group restricts the division and maturation of vascular endothelial cells, 25 leading to a decrease in the submucosal vessels in the urethra. Additionally, there were more vaginal deliveries in the PostM group than in the PreM group, which can cause damage to the urethral tissue and the blood vessels embedded in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Im Einklang mit dieser Hypothese wurde nach Verabreichung eines Aromatasehemmers an trächtige Stuten, die zu einer erheblichen Reduktion der plazentaren Östrogenproduktion führte, eine Reduktion des Geburtsgewichts der Fohlen [49] sowie Veränderungen in der plazentaren Expression einiger Gene mit Bedeutung für die Angiogenese beobachtet [50]. Weiterhin gibt es Hinweise, dass die plazentaren Östrogene an der Regulation der plazentaren und uterinen Durchblutung beteiligt sind [51]. Allgemein ist die Vorstellung verbreitet, dass ein "Östrogenanstieg" am Ende der Gravidität zusammen mit dem präpartalen Progesteronabfall zu einer fortschreitenden Verschiebung des "Östrogen-/Progesteronverhältnisses" führt und schließlich das Überschreiten eines kritischen Schwellenwertes entscheidend für den Geburtseintritt sein soll.…”
Section: öStrogeneunclassified
“…Distinct regions of the murine placenta are shown in Fig 4a . The placenta is made up of maternal decidua, the fetal-derived junctional zone, and the meshed maternal-fetal vascular interface (labyrinth). 48 Figures 5b and 5c depict immunofluorescence staining in which blue is a stain for cell nuclei (DAPI), red indicates the endothelial cell marker CD31, and green is pimonidazole which is used to assess hypoxia. The CD31 signal (Figs.…”
Section: Ko Placentae Have Higher Calcification and Hypoxia Compared ...mentioning
confidence: 99%